Географічна структура урбанофлори Харкова - Звягінцева, К.О. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2014)
Осуществлен географический анализ урбанофлоры Харькова (согласно классификации Ю.Д. Клеопова). Выделено
13 типов геоэлементов с 32-мя геоэлементами. Географическая структура урбанофлоры свидетельствует о ее бореально-субсредиземноморско-европейском характере с примесью евразийско-южносибирских и номадийских элементов.
Зональный характер урбанофлоры отображают европейский, евразийский, голарктичный, номадийский типы географических элементов. The article presents results of geographical analysis of the
Kharkіv urban flora. Following Yu. Kleopov’s classification of
geoelements, 13 types of geographic ranges consisting of 32 geoelements
are distinguished. The geographical structure of the
Kharkiv urban flora features Boreal Submediterranean and European
characters, as well as Eurasian and South Siberian ones,
with some alien influenсe. The zonal character reflects the European,
Eurasian, Holarctic, and Nomadic types of geoelements of
the urban flora.